USING CAPM AND FAMA-FRENCH THREE-FACTOR MODEL TO EXPLAIN STOCK PERFORMANCE IN RUSSIA (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Almost all investors want to be able to predict stock returns that will occur in the future. This will enable them to make focused bets and earn higher returns in comparison to those who do not possess this information. To this end, investors can rely on different asset pricing models and two of the most popular choices made are the capital asset pricing model (or the CAPM) and the Fama-French three-factor model. This study tries to compare the CAPM with the three-factor model for individual securities using panel data from 2018 to 2023 on the common shares of 114 companies listed on the Russian stock exchange.